2017
DOI: 10.1021/acs.jpcc.7b07611
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation and Site Speciation for Alloyed Palladium–Platinum Model Catalysts Studied by in Situ FTIR Spectroscopy

Abstract: In situ Fourier transform infrared spectroscopy was used to study transient CO oxidation over a series of bimetallic Pd−Pt catalysts with different Pd:Pt molar ratios. The catalysts were found to contain both alloyed PdPt nanoparticles (particle sizes 25−35 nm) and monometallic Pd nanoparticles (sizes below 10 nm). For oxygen-free conditions, CO reduces the surface while simultaneously function as a chemical probe molecule whereby the CO adsorption sites can be characterized. Under these conditions, it is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…With the common assumption of similar extinction coefficients for the different CO species, the relative presence of the different CO species can be determined. For the catalysts with high dispersion, the bar graph in Figure c shows that a significant amount of bridge and 3-fold hollow bonded CO species occupies the Pd sites in line with previous results, giving rise to a stoichiometric factor (SF) of 2.2 Pd atoms per CO molecule. For Pd/γ-Al 2 O 3 -900 with larger Pd particles, some spectral differences are seen.…”
Section: Resultssupporting
confidence: 89%
“…With the common assumption of similar extinction coefficients for the different CO species, the relative presence of the different CO species can be determined. For the catalysts with high dispersion, the bar graph in Figure c shows that a significant amount of bridge and 3-fold hollow bonded CO species occupies the Pd sites in line with previous results, giving rise to a stoichiometric factor (SF) of 2.2 Pd atoms per CO molecule. For Pd/γ-Al 2 O 3 -900 with larger Pd particles, some spectral differences are seen.…”
Section: Resultssupporting
confidence: 89%
“…Adsorption of CO on palladium (and noble metals in general) often results in a variety of adsorption configurations including linearly bound and different types of bridge-bonded CO species. 47 Their relative presence depends on the palladium particle morphology. This is commonly accounted for by inferring a stoichiometric factor (F S ) correlating the number surface palladium atoms probed by one CO molecule.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…For catalytic oxidation of both CO and CH 4 , palladium is often the element of choice when designing the active component of the catalyst. Under oxidizing conditions at low temperatures, Pd-based catalysts typically undergo oxidation such that PdO develops, which becomes the active component in practice. For ideal single crystals, it has been shown that a thin layer of PdO(101) can form on the PdO(100) surface when exposed to oxygen. The PdO(101) surface exposes under-coordinated Pd atoms that excel the catalytic activity for both CO , and CH 4 oxidation. , If the PdO layer grows too thick, a nonepitaxial growth takes over such that a polycrystalline PdO develops, which has a low catalytic activity .…”
Section: Introductionmentioning
confidence: 99%